Małżeństwa wiejskie w Polsce lat osiemdziesiątych. Szkic historyczny - Nowak,Waldemar (Wydawnictwo Naukowe UAM, 2000)
In the article I present the structure of rural marriage in Poland of the 80-ies. I analyse basic factors of marriage mating, especially the reasons for getting married. Among the most important reasons are: love, material reasons, friendship, prestige, social position, sex. The article includes also the results of the research on marriage durability (stability), and also on factors influencing the marriage success or failure.
Rural marriages in Poland of the 80-ies. Historical study